A single-cell landscape of the regenerating spinal cord of zebrafish - Lei Yao; Xinyi Cai; Saishuai Yang; Yixing Song; Lingyan Xing; Guicai Li; Zhiming Cui; Jiajia Chen (Neural Regeneration Research)
Unlike mammals, zebrafish possess a remarkable ability to regenerate their spinal cord after injury, making them an ideal vertebrate model for studying regeneration. While previous research has identified key cell types involved in this process, the underlying molecular and cellular mechanisms remain largely unexplored. In this study, we used single-cell RNA sequencing to profile distinct cell populations at different stages of spinal cord injury in zebrafish. Our analysis revealed that multiple subpopulations of neurons showed persistent activation of genes associated with axonal regeneration post injury, while molecular signals promoting growth cone collapse were inhibited. Radial glial cells exhibited significant proliferation and differentiation potential post injury, indicating their intrinsic roles in promoting neurogenesis and axonal regeneration, respectively. Additionally, we found that inflammatory factors rapidly decreased in the early stages following spinal cord injury, creating a microenvironment permissive for tissue repair and regeneration. Furthermore, oligodendrocytes lost maturity markers while exhibiting increased proliferation following injury. These findings demonstrated that the rapid and orderly regulation of inflammation, as well as the efficient proliferation and redifferentiation of new neurons and glial cells, enabled zebrafish to reconstruct the spinal cord. This research provides new insights into the cellular transitions and molecular programs that drive spinal cord regeneration, offering promising avenues for future research and therapeutic strategies.